Resistance training with blood flow restriction on vascular function: A meta-analysis - Liu, Y.; Jiang, N.; Pang, F.; Chen, T. (International Journal of Sports Medicine, 2021)
In this meta-analysis, the aims were to examine the effects of resistance training with and without blood flow restriction on vascular function. Five databases were searched up to June 2020 for papers about resistance training with blood flow restriction influence on vascular function. The quality of each identified study was evaluated. Effect sizes were estimated in terms of the standardized mean difference. A subgroup analysis was conducted according to participants` age, training duration, and cuff pressure. The results of six studies on arterial compliance and five on vascular function were highly homogenous regarding responses to resistance training with or without blood flow restriction. Resistance training with blood flow restriction had a more positive effect for regulating arterial compliance than resistance training without blood flow restriction, but not for vascular function. Resistance training with blood flow restriction leads to a more positive effect on vascular function than resistance training when training for no longer than four weeks.